Penerapan Metode Pembiasaan Dalam Meningkatkan Kedisiplinan Anak Melaksanakan Shalat Lima Waktu di Taman Pendidikan Al-Qur`an Mamba`ul `Ulum Seketeng Sumbawa Besar - Muji Agus Sofiyandi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
Education is a very important means of creating the best possible human resources. It should be done seriously and responsibly. In order to make education a success, teachers must be able to foster students' disciplined attitudes, especially self-discipline. TPQ Mambaa`ul `Ulum Seketeng Sumbawa Besar is one of the educational institutions that researchers view as a madrasah diniayah which implements habituation methods in the educational process, one of which is increasing children's discipline in performing the five daily prayers. Applying the habituation method to improve the discipline of praying five times a day is certainly not easy and has obstacles, especially if it is applied to elementary or middle school level children who are still teenagers. However, in this way, ustadz and Koran teachers must find solutions to these obstacles so that the aim of implementing the habituation method can be achieved. That is why most of the TPQ Mamba`ul `ulum students are very concerned about the discipline of praying five times a day. Based on our observations and reality in the field, one of the inhibiting factors and obstacles is that children at home are not instructed by their parents to pray in congregation.